“Till I in hand her yet halfe trembling tooke”: Doctrines of Justification in Edmund Spenser’s Amoretti - Shufran, Lauren (Renaissance and Reformation / Renaissance et Réforme, 2018)
This article claims there is an underlying soteriological conceit in Spenser’s Amoretti (1595) concerning the roles that “works” and “grace” play in the beloved’s requital: roles with theological analogues in justification, the means by which people were declared righteous before God. I show how Spenser’s lover struggles with works-righteousness, and how Spenser betrays “Protestant” thought about the inadequacy of works even as his lover insists upon them. Spenser’s lover fails repeatedly in his labours until grace comes to him, unwilled, in a moment of concession. His “works” afterward become meaningful—but only according to the reformed understanding by which good works come after faith. Still, a doctrinal line cannot be perfectly drawn, since requital is effected through poetic labour. I propose this irresolution is a consequence of Spenser’s attention to Paul’s Epistles, and their occasional affirmations of the usefulness of law despite their overwhelming insistence on grace. It also stems from the lack of a reformed doctrinal consensus about the role of works after justification.